2017
DOI: 10.1002/polb.24310
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport properties of mechanically stable symmetric ABCBA pentablock copolymers with quaternary ammonium functionalized midblock

Abstract: Anion exchange membranes (AEMs) are a promising class of materials for applications that require selective ion transport, such as fuel cells, water purification, and electrolysis devices. Studies of structure–morphology–property relationships of ion‐exchange membranes revealed that block copolymers exhibit improved ion conductivity and mechanical properties due to their microphase‐separated morphologies with well‐defined ionic domains. While most studies focused on symmetric diblock or triblock copolymers, her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(105 reference statements)
2
13
0
Order By: Relevance
“…Solid lines are Park model fitting.Mechanical properties. The stress-strain characteristics of HMT-PMBI, PPO-TMA and PPO-AGO changed between drier and wetter conditions at 60 o C, which agrees with other AEMs and PEMs 76,[85][86][87][88][89]. By using two different humidities, the range of mechanical properties of a film can be captured within the context of the water uptake study; a more exhaustive study81 was not completed as it is outside of the scope of this work.…”
supporting
confidence: 69%
“…Solid lines are Park model fitting.Mechanical properties. The stress-strain characteristics of HMT-PMBI, PPO-TMA and PPO-AGO changed between drier and wetter conditions at 60 o C, which agrees with other AEMs and PEMs 76,[85][86][87][88][89]. By using two different humidities, the range of mechanical properties of a film can be captured within the context of the water uptake study; a more exhaustive study81 was not completed as it is outside of the scope of this work.…”
supporting
confidence: 69%
“…However, AAEM conductivity is significantly influenced by hydrophobic-hydrophilic microphase separation, because a well-defined polymer morphology (e.g., bicontinuous hydrophobic-hydrophilic channels) facilitates water/hydroxide transportation in solid-state membranes (14). In previous reports, modifying polymer morphology with multiblock sequences (15)(16)(17)(18), long flexible side chains (18)(19)(20)(21), or microporous structures (22) has improved hydroxide conductivity. For instance, Watanabe and coworkers (15) observed that multiblock poly(arylene ether)s showed significantly higher hydroxide conductivity than their random copolymer analogs [σ (OH − , 60°C) = 126 mS/cm and 35 mS/cm for multiblock and random copolymers, respectively.…”
mentioning
confidence: 99%
“…An ideal Young's modulus value can occur over the broad range of~65-450 MPa, where handling was found to be easier according to Ertem et al, no fluid-like behavior was observed, and ruptures due to physical contact were not observed [105]. Below 65 MPa, the membrane can be more fluid-like, and above 450 MPa, the membrane can be very stiff [106,107]. Another important requirement is to keep Young's Modulus difference to a minimum at 25 and 60 • C. Nafion 115 meets these requirements with the values of 288.94 and 221.46 MPa at 25 and 60 • C, respectively.…”
Section: Tensile Strengthmentioning
confidence: 99%